Optimizing micropropagation of Indonesian conserved orchid Vanda celebica using organic compounds and a temporary immersion system - Ainna N. LAILY; Awang MAHARIJAYA; Dyah R. WULANDARI; Dwi M. PUSPITANINGTYAS; Siti R. ARIATI; Andri F. MARTIN; Betalini W. HAPSARI (Notulae Botanicae Horti Agrobotanici Cluj-Napoca)
Vanda celebica is an orchid species endemic and protected in North Sulawesi, Indonesia. To overcome such difficulties, micropropagation methods have been widely used, incorporating modified media and culture systems to improve success rates. Therefore, this study aimed to evaluate the viability of dry seeds stored at -20 °C for five years and the micropropagation of their protocorms using organic compounds, enhanced by a temporary immersion system (TIS) bioreactor. The genetic similarity between regenerants and the parental plant was also assessed using inter-sequence simple repeats (ISSR) markers to support conservation efforts. The results showed that V. celebica seeds stored for five years retained viability, with germination rates ranging from 56.16% to 73.45%. The addition of 40 g L-1 potato puree to the germination media significantly enhanced protocorm development. For further proliferation, ½-MS media supplemented with 150 ml L-1 coconut water and 50 ml L-1 carrot juice was found to be the most effective, resulting in a protocorm-like body (PLB) induction rate of 2.22 per explant, with an initiation time of 14.43 weeks, a 96.54% survival rate, and 30.56% of explants successfully induced. Dividing stage-4 protocorms yielded the best response, producing an average of 4.54 induced explants with an initiation time of 8.18 weeks. The TIS bioreactor system showed optimal results for shoot regeneration, achieving 64.84% and 37.07% regeneration rates. Genetic analysis indicated a similarity coefficient of 0.74-0.89 between regenerants and the parental plant, suggesting a genetic diversity comparable to Vanda species in their natural habitat.